Systemic lupus erythematosus - Lahita, Robert G. (Robert George), 1945- (Academic Press, 2004)
Systemic Lupus Erythematosus, Fourth Edition, provides an understanding of the basic mechanisms as well as the diagnostic and therapeutic aspects of lupus. Four-color illustrations throughout, this book is attractive to both the investigative community and clinicians. As lupus has become a paradigm for the study of autoimmune disease, immunologists investigating autoimmunity are becoming more interested in lupus. Basic immunology of phospholipid antibodies, clotting abnormailities, and newest methods of therapy of antiphospholipid syndrome are given in this newest edition of a classic reference. * Comprehensive current coverage of basic models of etiology and pathogenesis * Complete catalog of autoantibodies produced * Includes an outstanding review of imaging techniques for the diagnosis of lupus and its complications for each organ system * Includes CD-ROM of images excellent for teaching purposes and downloading into presentations.